The role of national employment programs in the personal and professional development of job seekers in Algeria. – Study of the State of graduates of higher education who are placed under graduates insertion contract ( CID )in the secondary education inst - Smaili, Mahmoud; Benamara, Saida (Milev Journal of Research and Studies, 2022)
The aim of this study was to diagnose the reality of the phenomenon of national employment programs in Algeria as one of the main axes of the national employment strategy .which qualifies it to be a vital and appropriate field that helps to understand the reality of these programs in all its dimensions. Especially the programs designated to the personal and professional development for graduates of the higher education. In this sense, this study attempted to answer the following main question: - What is the role of national employment programs in the personal and professional development of job seekers of graduates higher education? In order to answer this question, a number of hypotheses were formulated, analyzed and discussed. Descriptive methods were used. As for the place of study, it was determined in the secondary education institutions of wilaya of Mila. Data collection was distributed to all graduates of higher education placed in (CID) in secondary education institutions in the year of 2015. The most important findings were that the work in (CID) has contributed positively to their personal and professional development, which enabled them to settle and continue in this program.